Wielka Wojna, lasy, owady i uczeni. Krajowa stacja doświadczalna dla badania szkodników zwierzęcych na roślinach przy Zakładzie Zoologicznym Uniwersytetu Jagiellońskiego w latach 1916–1923 - Kargol, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
W czasie I wojny światowej działania wojenne przyniosły na terenie Galicji bezpośrednie zniszczenia lasów oraz rozwój szkodników leśnych, spowodowany zmniejszoną troską o drzewostan. Jednymi z najgroźniejszym owadów stały się wówczas poproch cetyniak atakujący lasy w Puszczy Sandomierskiej oraz kornik drukarz niszczący drzewostan w Tatrach. W 1916 r. z inicjatyw galicyjskiego Namiestnictwa powołana została przy Zakładzie Zoologicznym Uniwersytetu Jagiellońskiego specjalna instytucja do ochrony lasów przed owadami o nazwie „Krajowa stacja doświadczalna dla badania szkodników zwierzęcych na roślinach”, z dr. Ludwikiem Sitowskim na czele. Koncentrowała się na działalności naukowo-badawczej i informacyjno-publicystycznej.

The article discusses the impact of the warfare on the natural environment specially forests in Austrian Galicia in years 1914–1918. Forests were devastated by fires, gunfire and forest pests such as European spruce bark beetle in forests in the Tatra Mountains and pine looper in the Sandomierz Forest. In 1916 was established the experimental station for the study of animal pests on plants at the Institute of Zoology of the Jagiellonian University. The head of this institution was Ludwik Sitowski Ph.D., a Polish researcher, zoologist and entomologist. This text undertakes various issues: the destruction and reconstruction of forests in Galicia, forest pests, the activity of entomologists at Jagiellonian University, and the activity of the experimental station and Sitowski's publications about insects.
The Great War, forests, insects and scientists. National experimental station for the study of animal pests on plants at the Zoological Department of the Jagiellonian University in the years 1916–1923
Keywords: I wojna światowa; lasy; owady; Uniwersytet Jagielloński; entomologia; Ludwik Sitowski; World War I; (Austrian) Galicia; forests; insects; the Jagiellonian University; entomology